Global change, ecosystems, sustainability theory, methods, practice - Mukhopadhyay, Pranab; Das, Kalyan; Nawn, Nandan (SAGE Publications, Inc., 2017)
It is impossible to ignore the connection between economic development and ecological sustainability- overwhelming scientific evidence points to anthropogenic pressures slowly destroying life on Earth. The need for corrective action is, therefore, critical